COLOR AS A TOOL OF EMOTIONAL IMPACT IN REPORTAGE AND LANDSCAPE PHOTOGRAPHY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Color is a key expressive medium in photography, influencing viewer perception and emotional response. In reportage and landscape photography, color can not only enhance content but also create a specific mood, direct attention, and evoke associations. This article analyzes the psychological mechanisms of color perception, the specifics of its application in various genres of photography, and examines the practical aspects of using a color palette to enhance emotional impact.